Experimental and Theoretical Investigation of Impact Dynamic Plasticity for CK45 - Ameen, Hani Aziz; Abd Alameer, Ahlam (Al-Khwarizmi Engineering Journal, 2014)
Abstract This paper represents a study of the effect of the soil type, the drilling parameters and the drilling tool properties on the dynamic vibrational behavior of the drilling rig and its assessment in the drilling system. So first, an experimental drilling rig was designed and constructed to embrace the numerical work. The experimental work included implementation of the drill-string in different types of soil with different properties according to the difference in the grains size, at different rotational speeds (RPM), and different weights on bit (WOB) (Thrust force), in a way that allows establishing the charts that correlate the vibration acceleration, the rate of penetration (ROP), and the power consumption curves with the depth of drilling. In addition to that the ANSYS Workbench (the 14.0 release) software was used to simulate and verify the experimental results. And it was also used to model other numerical cases with different drill bit diameters. Keywords: Soil, Vibration, and Drilling Rig.